Studies on local mango- and noniderived milk curds and their biological activities - Norliana, Munir (2021)
The dairy market has grown favourably with constant growth rates in Malaysia in the past years. However, certain controversies surrounding the use of calf rennet as milk coagulant has encouraged the search for its alternatives, especially of plant origins. Hence, the study aims to investigate local plants having a dual effect of coagulating and fortifying milk simultaneously. In this study, ten samples from nine plants have been screened for the best two potential rapid milk coagulant. A total of three plants exhibited positive results on milk coagulation, with M. citrifolia juice extract showed the fastest coagulation time (10.8 ± 0.36 s) followed by M. indica seed kernel extract (28.8 ± 0.61 s) and T. catappa leaf extract (40.73 ± 1.91 s). Two plants proceeded with the further tests of determining the coagulant action by investigating the protein presence within extract through size exclusion chromatography, Bradford protein assay, SDS-PAGE analysis, and LCMS analysis. Both plants were proven to coagulate milk by enzyme action, with M. citrifolia was having definite proof of possessing protease-like enzyme (cysteine protease) with a molecular size of approximately 30 kDa. Then, the milk curd derived from both extracts of M. indica and M. citrifolia were further tested on their antioxidant and antidiabetic properties. The assays of TPC, DPPH, and FRAP were performed in determining the antioxidant activity of the milk curd. The result showed M. indica-added milk curd was having higher total phenolic content (34.7 ± 0.49 mg GAE/g) and antioxidant capacity of FRAP assay (317.16 ± 0.99 mg GAE/g), and the lower IC50 value for DPPH assay (12.31 ± 0.66 µg/mL) compared to M. citrifolia-added milk curd. Antidiabetic properties were assessed via α-amylase and α-glucosidase in vitro inhibitory activity assays. M. indica-added milk curd shown to have lower IC50 value in both assays compared to M. citrifolia-added milk curd, with 354.6 ± 20.26 µg/mL for α-amylase inhibitory assay and 4.86 ± 0.16 mg/mL for α-glucosidase inhibitory assay. Based on overall evaluations, M. indica was a better coagulant and fortifier of biological activities than M. citrifolia, and both plants found with the added advantage of being a fortifier compared to the rennet of only able to coagulate milk. The study showed the potential of local plants as milk coagulants as well as having benefits of biological activities and if developed into yogurt or cheese products, able to encourage the local dairy industry.